Management And Eradication Of The Criminal Act Of Togel Gaming In The Police Jurisdiction - Mesias Jusly Penus Sagala (Eduvest - Journal of Universal Studies, 2022)
This study aims to determine the causes of the rampant lottery gambling in the jurisdiction of the Pematang Siantar Police and the countermeasures carried out by the Pematang Siantar Police in eradicating the crime of lottery gambling in the jurisdiction of the Pematang Siantar Police. The data used in this study are primary data and secondary data. The results showed that the factors causing the rampant lottery gambling in the Pematang Siantar Police Legal Territory were: low level of education, low economic capacity with high unemployment, environmental factors where people like to play gambling and cultural factors. The educational factor as an individual factor is very influential on the factors causing the occurrence of gambling crimes, but besides individual factors, what is even more important are factors outside the individual, namely the economy, environment and culture where a person lives and socializes with other individuals. The countermeasures carried out by the Pematang Siantar Police to eradicate the crime of lottery gambling are: (a) preventive efforts and (b). countermeasures (repressive).